2022
DOI: 10.3390/nu14061272
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri CCFM8631 Alleviates Hypercholesterolaemia Caused by the Paigen Atherogenic Diet by Regulating the Gut Microbiota

Abstract: Cardiovascular disease has one of the highest global incidences and mortality rates. Atherosclerosis is the main cause of cardiovascular disease, and hypercholesterolaemia and hyperlipidaemia are the main risk factors for the development of atherosclerosis. Decreasing serum cholesterol and triglyceride concentrations is considered to be an effective strategy to prevent atherosclerotic cardiovascular disease. Previous studies have shown that many diseases are related to gut microbiota dysbiosis. The positive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…L. reuteri serves as a probiotic to modulate periodontal parameters and subgingival biofilm dysbiosis by resolving inflammation and by reducing the molecular mediators associated with bone loss ( Salinas-Azuceno et al., 2022 ). Furthermore, L. reuteri treatment was shown to protect liver function and recover liver superoxide dismutase concentrations in mice fed a Paigen atherogenic diet ( Wang et al., 2022 ). Therefore, our study suggested a reduction in beneficial bacterial taxa accompanied by a significant increase in potential pathogens in SBP patients leads to a more obvious dysbiosis of gut microbiota, resulting in disruption of intestinal barrier function and bacterial translocation.…”
Section: Discussionmentioning
confidence: 99%
“…L. reuteri serves as a probiotic to modulate periodontal parameters and subgingival biofilm dysbiosis by resolving inflammation and by reducing the molecular mediators associated with bone loss ( Salinas-Azuceno et al., 2022 ). Furthermore, L. reuteri treatment was shown to protect liver function and recover liver superoxide dismutase concentrations in mice fed a Paigen atherogenic diet ( Wang et al., 2022 ). Therefore, our study suggested a reduction in beneficial bacterial taxa accompanied by a significant increase in potential pathogens in SBP patients leads to a more obvious dysbiosis of gut microbiota, resulting in disruption of intestinal barrier function and bacterial translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al 50 found that Roseburia was the key bacterium for the antiatherosclerotic effect of berberine in ApoE -/- mice. Lachnospira_NK4A136_group was reported to be responsible for the alleviation of hypercholesterolemia 51 . Since these three genera belong to the short-chain fatty acid-producing bacteria, mechanisms by which these genera affect lipid metabolism have always focused on the improvement of lipid metabolism by short-chain fatty acids but lacked analysis of lipid metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It alleviates the imbalance of the gut microbiota caused by diseases through upregulating the content of beneficial bacteria and reducing pathogenic bacteria. A study showed that Lactobacillus reuteri CCFM8631 can increase the relative abundance of faecal Deferribacteres, Lachnospiraceae NK4A136 group, while Lactobacillus and Dubosiella decrease the relative abundance of Erysipelatoclostridium and Romboutsia in mice with cardiovascular disease [54]. In high-fat diet mice, the diversity of the gut microbiota and its composition were significantly changed after treatment with probiotics that contained LAB, the number of Lactobacillales, Clostridiales, and Bifidobacteriales was overrepresented while the phylum Verrucomicrobia was absent and the number of Proteobacteria was significantly lower in the probiotic-treated group compared to placebotreated high-fat diet fed mice [55].…”
Section: Effects Of Lab On the Gut Microbiota Lab Promote Stability O...mentioning
confidence: 99%